Ambiências memorialísticas mítico- midiáticas: um estudo sobre a comunicação e o consumo de eventos ligados à cultura de fãs - Silva, Wagner Alexandre (2022)
There are countless figures, materialities and extraordinary universes that emerged from contemporary media narratives and products that are intertwined with fan culture. Originated by pop culture (books, movies, series, comics, games, music, sports, radio and TV programs, digital media, etc.) and serving as inspiration and aspirational models, we have observed an increasing number of deferences being performed by fans and fandoms for mediatic myths, which is very similar to devotional behaviors performed by believers, devotees and adepts of the most different doctrines and religious practices. Assuming that the fascination culminates in different modes of interaction with a different type of sacred (neosacralities) and in the establishment of specific social ritualistic patterns, in the present research, we seek to point out the similarities and differences between the experiences had by believers in religious spaces of devotion. and those provided to fans by the spaces presented in the Brazilian memorial event known as CCXP. To promote such evaluations, the work is theoretically based on Mircea Eliade's (1972, 1979, 1992, 2008, 2018) conceptualizations and arguments about myths and hierophany; semiosphere by Yuri Lotman (1996); Mônica Nunes (1993, 2001, 2019); neoreligiosity by Matt Hills (2002); show by Guy Deborb (2000); atmospheres by Jean Baudrillard (1973) and Norval Baitello Jr (2010); senses by David Le Breton (2016); collective memory of Maurice Halbwachs (2013); Johan Huizinga's play (1971); Schechner's performance and rituals (2012); mediatization of culture by Stig Hjarvard (2014); communication and consumption by Maria Aparecida Baccega (2008); material culture by Daniel Miller (2013); Edgar Morin's Olympians (1997); fan culture by Adriana Amaral (2011, 2016), Mônica Nunes (2012, 2015, 2017), among other authors. Following this endeavor, we added audiovisual records collected through participant observations and observer participations carried out in the editions of the years 2014, 2015, 2016, 2017, 2018 and 2019 and information obtained from websites, blogs and social networks on the Internet, in an attempt to answer the following question: What are the observable similarities and differences between the mythical-mediatic memorialistics atmospheres generated in CCXPs and those presented in religious devotional spaces? In order to achieve the purpose of this study, we promoted an analysis of religious devotional spaces and of the mythical-mediatic memorialistics atmospheres of the fairs, inferring that although there are notably characteristics that resemble the events to religious spaces, we observed that the difference between fans and faithful is contained in the production by the former, because unlike the religious, fans can represent and remodel their idols in their own way, that is, reinvent their stories, reimagine their worlds, change personalities, change their origins, their genres, incorporating elements that they wish, without such alterations being taken as an affront or disrespect to the objects of worship.